Respuesta :

Solve the equation:-

[tex]5(4x - 4) = 5(3x + 3) \\ \cancel5(4x - 4) = \cancel5(3x + 3) \\ (4x - 4) = (3x + 3) \\ 4x - 3x = 4 + 3 \\ x = 7[/tex]

Verification:-

Put the value of X in equation:-

LHS:-

[tex]5(4x - 4) = 5(4(7) - 4) \\ 5(28 - 4) \\ 5(24) = 120[/tex]

RHS:-

[tex]5(3x + 3) = 5(3(7) + 3) \\ 5(21 + 3) \\ 5(24) = 120[/tex]

LHS= RHS

Hence proved

Answer:

x = 7

Step-by-step explanation:

Divide by 5 on each side :

  • 5/5 (4x-4)=5/5 (3x+3)​
  • 4x - 4 = 3x + 3

Add 4 on each side :

  • 4x - 4 + 4 = 3x + 3 + 4
  • 4x = 3x + 7

Subtract 3x from each side :

  • 4x - 3x = 3x + 7 - 3x
  • x = 7
ACCESS MORE